A warrior invoking raudram rasa (fury/rage) - Temples of India Project Team (Jio Institute, 2024)
This panel depicts a warrior invoking raudram rasa (fury/rage) by aggressively wielding a drawn sword. The theme may be based on the medieval miniature painting of the Ragamala series. Ragini Lalita has a similar theme where the king departs for an expedition and the women of the palace convince him to stay. The central figure of a warrior-king is aggressively stepping forward wielding a naked sword in his right hand. A dagger is tucked into his kamarbandha (waist belt). The central female figure (seen on the left) may be a queen, who is trying to stop the man by pulling him behind. Another lady is standing in front of the man (seen on the right) and sporting long braided hair, but with her face and hands damaged. On the ground, between the feet of the man, a small figure (likely a servant) is grovelling for mercy.